Acts of Desperation - Nolan, Megan (London Jonathan Cape, 2021)
The female narrator falls completely into the power of a male writer. When he suddenly rejects her, she resolves to hang on to him and his love at all costs ... even if it destroys her.
Keywords: Man-woman relationships